Traffic Woes, Metro Manila, and Collaborative Problem-Solving: A Case Study of Computer-mediated, Collaboratively Built Information Infrastructure in the Field of Transportation in the Philippines - Joshua Ramon Enslin (IKAT: The Indonesian Journal of Southeast Asian Studies, 2018)
The chaotic traffic situation in Metro Manila has been characterized as a major roadblock to the country’s economic development and has turned into an important discussion point in political debates. In this paper three traffic related web services, aimed at helping their users gain an insight into the traffic situation of Metro Manila and beyond are analyzed in regards to their use of cooperation using Benkler’s concept of Collaborative Peer Production. The three web services differ starkly from each other in their concept – PH-Commute.com is a blog, Taxikick.com is a service for short messages pertaining to misbehaviors of taxi drivers, Sakay.ph is a navigation service. As I conclude, all three however share in common that they are indeed highly dependent on cooperation on different layers. Determined by the underlying concept of each of the websites, they incorporate inputs from their users, but they might also let their users help them in developing their software by publishing their source code, and they rely on community-created, open-source software infrastructure to be able to run their own.